Tri Hita Karana Philosophy in Ethical Leadership of Village Credit Institutions - Pramesti, I Gusti Ayu Asri; Renaldo, Nicholas (First Ciera Publisher, 2023)
Bali has several institutions based on cultural values, traditions and customs. Tri Hita Karana is a basic concept used by indigenous people in Bali as a guide in living life. The concept of Tri Hita Karana is also a foundation in organizations, one of which is the Village Credit Institution (LPD) in Bali. The Village Credit Institution is an institution formed by the village that functions to manage village finances with the aim of improving welfare. The success of LPD cannot be separated from the ethical role of the leaders. This article aims to provide an understanding of the philosophy of Tri Hita Karana in ethical leadership from the perspective of the philosophy of science ontology, epistemology, and axiology.